Heavy metals in water, sediment and tissues of Liza saliens from Esmoriz-Paramos lagoon, Portugal. - Fernandes, Conceição (2011)
http://apps.isiknowledge.com/full_record.do?product=UA&search_mode=GeneralSearch&qid=5&SID=T2n6@BOd@6lKkDK3EB3&page=1&doc=1&colname=WOS